Scoping review: The state of research on cryptogenic organizing pneumonia therapeutics. (December 2022) - Lau, Christopher; Liang, Brannen; Hovsepyan, Ourfa; Shreves, Tom; Wei, Kenneth
Abstract: Cryptogenic organizing pneumonia is a diffuse interstitial lung disease that starts in the alveolar wall and subsequently expands to the alveolar ducts and respiratory bronchioles. Randomized controlled trials are lacking to guide the treatment of cryptogenic organizing pneumonia, so treatment decisions and practice guidelines are often based upon observations from case series or expert clinical opinions. The backbone of treatment involves immunosuppression via corticosteroids. In refractory cases, cytotoxic therapy is considered. The evidence that supports the use of these regimens are limited. The goal of this scoping review is to conduct a systematic search of the literature to determine what regimens have been utilized to treat steroid refractory organizing pneumonia and to characterize the evidence supporting their use.